Case report: Immunotherapy guided by molecular profiling of tumors: illustrative cases and literature review - Ozdogan, Mustafa; Papadopoulou, Eirini; Metaxa-Mariatou, Vasiliki; Kapetsis, George; Meintani, Angeliki; Florou-Chatzigiannidou, Chrysiida; Yildiz, Akin; Cakir, Muharrem Okan; Kirca, Onder; Nasioulas, George (Frontiers in Medicine, 2024)
Predictive biomarkers are necessary for the identification of immunotherapy-responsive patients. Tumor mutation burden (TMB), as determined by next-generation sequencing (NGS), and PD-L1 expression, as evaluated by Immunohistochemistry (IHC), are the biomarkers most frequently employed in clinical practice. In addition, microsatellite instability (MSI) was the first biomarker to demonstrate immunotherapy efficacy irrespective of the type of tumor and possesses a high predictive value. However, its limited use across most tumor types limits its therapeutic potential. This report describes two cancer patients with positive TMB and PD-L1 expression. The molecular profile of the tumor indicated that the first patient was responsive to Immune checkpoint inhibitors (ICI), while the second patient was resistant. These case studies demonstrate that tumor molecular analysis in combination with immunotherapy predictive biomarkers, such as PD-L1 expression and TMB, can enhance the prediction of response to ICI for specific patients. This methodology enables an individualized and improved approach to the treatment and management of the disease.